Digital Certificate Authority with Blockchain Cybersecurity in Education - Giandari Maulani; Gunawan Gunawan; Leli Leli; Efa Ayu Nabila; Windy Yestina Sari (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2021)
In the 21st century the development of internet technology has experienced explosive developments with complex threats in Higher Education. Cyber ​​security is a priority issue for all countries by using data and communication technology in various aspects of life. In order to advance and improve the digital economy in the implementation of a comfortable and reliable electronic system with methods of increasing competitiveness, cyber innovation also builds understanding and sensitivity to national security and resilience. Cybersecurity is constantly changing and learning providers often do not have the authority or facilities and capacity in various activities that connect students, in ensuring their knowledge and expertise. In carrying out the provision and validation of qualifications that are tried exclusively at the centralized management of learning institutions or employing institutions, these days have more ownership of learning experiences with results without risking safety, security and accessibility. This validation provision is not prolonged because learning is far more international than before and education continues to frequently use online platforms. Education providers offer degree internships that represent a new method of expertise and provide a route of advancement in increasing employability prospects. Blockchain is a digital and decentralized ledger, encompassing a set of interlocking technologies. Blockchain is designed to transform the centralized as well as validation model to a decentralized ledger from a secure database. These databases are shared, replicated, and synchronized for validation at universities, legal or regulatory agencies and industrial bodies across the internet.